Current flow mechanisms in p-i-n structures based on cadmium telluride - Gorley, P.M.; Demych, M.V.; Makhniy, V.P.; Horvath, Zs.J.; Shenderovsky, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Electrical properties of p-i-n-structures obtained with low-temperature oxygen and lithium diffusion into low-resistive n-CdTe substrates have been investigated. The role of generation-recombination processes as well as trapping, impact ionization and overbarrier carriers transport in the dark current formation of samples studies have been defined.